The politics of intergovernmental transfers and local government deficits: Theory and evidence - Sanguinetti, Pablo J. (Estudios Económicos de El Colegio de México, 1993)
The purpose of this paper is twofold. First, we present a model of decentralized fiscal policy making where a "coordination failure" problem arises. Second, we make an effort in order to empirically test this approach by developing an empirical investigation based on the recent experience of two countries: Argentina and Great Britain.